IT Master Plan - Iwan Prasetiawan (ULTIMA InfoSys, 2019)
The rapid development of business, supported by technological developments that are not less rapid, it requires a strong and precise alignment between business strategies or organizations with the Information Systems (IS) strategy and Information Technology (IT)strategies as supporters. An IT strategy plan includes many aspects, covering several aspects which include aspects of technology architecture,roadmap / work plan, and supporting standards for its implementation. This Guidelines for Preparation and Implementation of the IT MasterPlan, explains the methods and main steps in managing and implementing IT strategy to support the implementation of the main tasks and the achievement of the strategic objectives of an organization or company. An important aspect that concern to the author is the importance of organizational and management involvement. Which is a key aspect of the planning process, together to ensure that all IS components have the same goals and direction as the business so it is easy to identify organizations that have not aligned. The logical relationship between business strategy and IT strategy does not usually occur directly, but through an intermediary for determining the IS Strategy, the strategy must be able to translate business strategies into the perspective of data and information flow to finally determine the information and communication technology work plan up to the specified year compiled in an IT Master Plan.